The association between perceived neighborhood social cohesion and intimate partner violence in a refugee camp in Dollo Ado, Ethiopia - Rebecca Hailu Astatke; Theodros Woldegiorgis; Jennifer Scott; Ndola Prata; Kim G. Harley; Negussie Deyessa; Anne Bennett; Vandana Sharma (Conflict and Health)
Abstract Background Intimate partner violence (IPV) is the most common form of gender-based violence affecting women and girls worldwide and is exacerbated in humanitarian settings. There is evidence that neighborhood social processes influence IPV. Perceived neighborhood social cohesion (P-NSC)—a measure of community trust, attachment, safety, and reciprocity—may be protective against women’s experience of and men’s perpetration of IPV and controlling behaviors. Methods A quantitative social network study, comprised of individual verbally-administered surveys, was conducted in Bokolmayo refugee camp in Dollo Ado, Ethiopia in 2019. In total, 302 Somali refugees (147 women and 155 men), sampled using snowball sampling, participated in the data collection. Logistic regression was used to examine P-NSC and its association with IPV to inform an IPV and HIV prevention intervention. Results Low P-NSC and men’s perpetration of physical IPV in the past month were strongly associated (adjusted AOR = 23.6, 95% CI: 6.2–89.9). Low P-NSC, conversely, was associated with decreased odds of women’s experiences of controlling behaviors by an intimate partner in the past year (AOR = 0.1, 95% CI: 0.0–0.5). Women’s experiences of other forms of IPV, including physical, sexual, and emotional IPV within the past year, were not associated with P-NSC in adjusted models; P-NSC was significantly associated with all forms of IPV in unadjusted models. Conclusion Social cohesion programs and other neighborhood approaches to improve P-NSC should be explored as potential avenues to prevent and reduce IPV, with a focus on male IPV and controlling behavior perpetration.